Research Progress on Physical Storage Methods of Toona Sinensis - Song Li; Benjiao Li; Binrong Ma; Yong Jing; Qiang Wang; Zheming Zhang (E3S Web of Conferences, 2021)
The toona sinensis (or Chinese toon) in rich in nutrition, with unique aroma and broad prospects for use. However, the toona sinensis is prone to respiration after being harvested. As a heat-sensitive vegetable, it is easy to lose water and decay. This paper introduced the latest research progress on physical preservation of toona sinensis before and during storage, providing references for developing new technologies of keeping Chinese toon fresh.